PENGARUH MOISTURE CONTENT DAN THERMAL CYCLIC TERHADAP SIFAT MEKANIK DAN FISIK KOMPOSIT HIBRID BERBASIS SERAT GELAS DAN COIR UNTUK APLIKASI PADA SUDU TURBIN ANGIN - , MASTARIYANTO PERDANA, ST ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Composites are materials that commonly used in engineering field. This is due to light weight and relatively strong properties. However, the synthesis fiber-based composites were not recommended due to environmental friendly. This research uses hybrid fiber composite with volume fraction at 12% of fiberglass, 18% of coir and 70% of epoxy. This study investigated the environmental influences (moisture content and thermal cyclic) on changes of mechanical and physical properties of hybrid composite. Composites were immersed in water by immersion time variations of 6, 12, 18, and 24 hours to determine the effect of moisture content. Hybrid composites were heated until 80ËC and then cooled in room temperture to determine the effect of thermal cyclic. Variations of thermal cyclic were 5, 10, 15, and 20 cycles. Test result shows degradation of mechanical properties of composite. Moisture content causes a decrease on mechanical properties of hybrid composite. For 24 hours of immersion time the reduction in tensile strength for effect moisture content was 39,94% of 65,474 MPa and impact toughness was 52,29% of 0,0163 J/mmÂ². Thermal cyclic also causes a decrease on mechanical properties of hybrid composite. For 20 cycles of thermal cyclic reduction in tensile strength was 32,44% of 65,474 MPa and impact toughness was 57,94% of 0,0163 J/mmÂ². Variation of dynamic loading was resulted stiffness degradation of hybrid composite. Stiffness degradation measured by ratio of E/Eô³ for the effect of moisture content (24 hours immersion) and thermal cyclic (20 cycles) were 30,00% and 15,15% respectively.